Screening and design of active metals on dendritic mesoporous Ce0.3Zr0.7O2 for efficient CO2 hydrogenation to methanol. (1st June 2022) - Alabsi, Mohnnad H.; Wang, Xilong; Zheng, Peng; Ramirez, Adrian; Duan, Aijun; Xu, Chunming; Huang, Kuo-Wei
Graphical abstract: Highlights: Novel dendritic PdZn/Ce0.3 Zr0.7 O2 (CZ) catalyst with small particle size was synthesized. Uniform dendritic morphology of PdZn/CZ can reduce the diffusion resistance of the reactants and products. PdZn/CZ possesses better hydrogen dissociation capability and higher adsorption and activation performance of CO2 . PdZn/CZ exhibits excellent CO2 conversion and high methanol yield. PdZn/CZ shows the superior 100 h long term stability of CO2 hydrogenation reaction. Abstract: Different active metals (PdCu, PdZn, CuZn, CuGa, and CuNi) over novel dendritic Ce0.3 Zr0.7 O2 (CZ) support were optimized to investigate their metal alloy interactions and further utilize their surface properties of the spherical morphology and the open pores of the dendritic support. The nature of the dendritic support offers a distinctive property in which it can increases the distribution of active sites. This variety of bimetallic phases withhold a distinctive interaction characteristic with the support that could promote CO2 hydrogenation to methanol by improving the oxygen vacancies and modifying the catalyst's reduction property. The addition of ZnO species into PdZn/CZ catalyst and the higher dispersion degrees of active metals could generate more oxygen vacancies that can improve and stabilize the methoxy species and promote the formate routes, thus, improve the activity of CO2 hydrogenation to methanol reaction. PdZn/CZ catalyst displayed the highest CO2 conversions (25.7 %), methanol yield (6.9 %), and superior 100 h long-term stability than those of other bimetallic catalysts. The best CO2 hydrogenation activity of the PdZn/CZ catalyst can be ascribed to the CO2 adsorption capabilities of CZ support that generated added oxygen vacancies and hydrogen dissociation performance of the Pd-ZnO active site.